2020
DOI: 10.1109/access.2020.3031022
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Evaluation of Multi-Mechanism Failure for Semiconductor Devices Using Physics-of-Failure Technique and Maximum Entropy Principle

Abstract: The physics-of-failure (PoF) technique is a practical approach to evaluate the reliability of semiconductor devices. However, the PoF approaches are usually insufficient in dealing with multimechanism failure and fitting the Monte Carlo (MC) sampling data. In our study, we propose an improved reliability evaluation method based on PoF technique and maximum entropy (MaxEnt) principle. The PoF models are used to generate time-to-failure samples of the failure mechanisms. Cumulative damage rules and competing fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Zuo et al [5] used the Engelmaier model, a strain-range-based fatigue model, to study the fatigue life of defective solder joints. Wan et al [6] proposed an improved reliability evaluation method based on PoF technique and maximum entropy (MaxEnt) principle. The results showed that the proposed MaxEnt distributions can generate more reliable reliability evaluation results compared with Weibull distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Zuo et al [5] used the Engelmaier model, a strain-range-based fatigue model, to study the fatigue life of defective solder joints. Wan et al [6] proposed an improved reliability evaluation method based on PoF technique and maximum entropy (MaxEnt) principle. The results showed that the proposed MaxEnt distributions can generate more reliable reliability evaluation results compared with Weibull distributions.…”
Section: Introductionmentioning
confidence: 99%
“…MEAs are especially popular in structural reliability analysis [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Their application goes much further, though; for example, MEAs used for the evaluation of the reliability of semiconductor devices [ 26 ]. MEAs have even been extended to multidimensional problems [ 27 , 28 , 29 , 30 ] and models in 2D domains and on surfaces [ 31 ].…”
Section: Introductionmentioning
confidence: 99%